2022
DOI: 10.3389/fendo.2022.896356
|View full text |Cite
|
Sign up to set email alerts
|

Low NAD+ Levels Are Associated With a Decline of Spermatogenesis in Transgenic ANDY and Aging Mice

Abstract: Advanced paternal age has increasingly been recognized as a risk factor for male fertility and progeny health. While underlying causes are not well understood, aging is associated with a continuous decline of blood and tissue NAD+ levels, as well as a decline of testicular functions. The important basic question to what extent ageing-related NAD+ decline is functionally linked to decreased male fertility has been difficult to address due to the pleiotropic effects of aging, and the lack of a suitable animal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…Physiological effects of low NAD + status and their potential impact on male fertility have been difficult to study due to a lack of suitable animal models. However, in recent studies, NAD + levels have been found associated with a decline of spermatogenesis in a transgenic mouse model and aging mice 27 .…”
Section: Introductionmentioning
confidence: 98%
“…Physiological effects of low NAD + status and their potential impact on male fertility have been difficult to study due to a lack of suitable animal models. However, in recent studies, NAD + levels have been found associated with a decline of spermatogenesis in a transgenic mouse model and aging mice 27 .…”
Section: Introductionmentioning
confidence: 98%